Calcium Signaling Pathway Genes RUNX2 and CACNA1C Are Associated With Calcific Aortic Valve Disease. (December 2015) - Guauque-Olarte, Sandra; Messika-Zeitoun, David; Droit, Arnaud; Lamontagne, Maxime; Tremblay-Marchand, Joël; Lavoie-Charland, Emilie; Gaudreault, Nathalie; Arsenault, Benoit J.; Dubé, Marie-Pierre; Tardif, Jean-Claude; Body, Simon C.; Seidman, Jonathan G.; et al.
Abstract : Background—: Calcific aortic valve stenosis (AS) is a life-threatening disease with no medical therapy. The genetic architecture of AS remains elusive. This study combines genome-wide association studies, gene expression, and expression quantitative trait loci mapping in human valve tissues to identify susceptibility genes of AS. Methods and Results—: A meta-analysis was performed combining the results of 2 genome-wide association studies in 474 and 486 cases from Quebec City (Canada) and Paris (France), respectively. Corresponding controls consisted of 2988 and 1864 individuals with European ancestry from the database of genotypes and phenotypes. mRNA expression levels were evaluated in 9 calcified and 8 normal aortic valves by RNA sequencing. The results were integrated with valve expression quantitative trait loci data obtained from 22 AS patients. Twenty-five single-nucleotide polymorphisms had P <5×10 −6 in the genome-wide association studies meta-analysis. The calcium signaling pathway was the top gene set enriched for genes mapped to moderately AS-associated single-nucleotide polymorphisms. Genes in this pathway were found differentially expressed in valves with and without AS. Two single-nucleotide polymorphisms located in RUNX2 (runt-related transcription factor 2), encoding an osteogenic transcription factor, demonstrated some association with AS (genome-wide association studies P =5.33×10 −5 ). The mRNA expression levels of RUNX2 were upregulated in calcified valves and associated with eQTL-SNPs. CACNA1C encoding a subunit of a voltage-dependent calcium channel was upregulated in calcified valves. The eQTL-SNP with the most significant association with AS located in CACNA1C was associated with higher expression of the gene. Conclusions—: This integrative genomic study confirmed the role of RUNX2 as a potential driver of AS and identified a new AS susceptibility gene, CACNA1C, belonging to the calcium signaling pathway. Abstract : Supplemental Digital Content is available in the text.